Literature Reviews: Role Situational Leadership in Improving Teacher Performance - Tuerah, Philotheus E A; Sumual, Shelty D.M.; Lumapow, Harol R.; Dondokambey, Rainier N; Dotulung, Reza A. W.; Paath, Deicy (JR Education, 2024)
Teacher performance plays a role in increasing student motivation and learning outcomes. This research aims to provide an overview of the relationship between situational leadership and performance. The research method used is qualitative with a literature review. Search for articles using Google Scholar with the keywords